PENERAPAN DAN PEMAKAIAN TEKNOLOGI INFORMASI SEBAGAI PENDUKUNG SISTEM PENGAMBILAN KEPUTUSAN (SPK) - Suyatno Suyatno (Universitas Islam Nahdlatul Ulama Jepara, 2005)
AbstractWith full of enthusiasm, province gevernments compete to implement informations technology in their with province. However; questioning ideas about the properness and the benefit of the program with infestation implantation rise.This proponent system of decision making will analyze the cost and advantages ofinformations technology in micro by using information Economic (IE) method, Marilyn 88.This method expands accounting system named ROI (Return On Investment) by adding two other domains which are; business and technology.With the result that we can make a conclusion whether informations technology service isfair or not by merging the business and technology and corporation factros. Keywords: information technology, information economic, ROI